Elaboración de objetos de aprendizaje utilizando el lego mindstorms ev3 para la operación de la suma, en la asignatura de matemática en el tercer año de educación general básica de la escuela ciudad de Zaruma, periodo 2016-2017. - Carvay Vacacela, Walther Vinicio (2018)
The present investigative process is based on a real problem that was found in the educational establishment "Ciudad de Zaruma" of the canton Zaruma province of El Oro, and that is the lack of incorporation of Education and Communication Technologies (ICT) in the classroom and technological equipment in the computer room of the school, which leads to the students' lack of interest in learning the mathematics subject. Therefore, it was proposed to develop Virtual Learning Objects (OVA), for the learning of the sum by using an educational robot (Lego MindsTorms Ev3), aimed at improving teaching in the mathematics subject. The OVA'S were developed based on the requirements and needs of the students and the teacher, applying the AODDEI methodology that allowed to take the whole process of development, evaluation and implementation, which counted on the participation of 17 students and a teacher of the matter. These OVA'S are aimed at learning the sum, since these resources allow retaking the subject of a subject and feedback to generate learning at all times with simple methods, able to adapt to the context of the student and can provide their benefit as it is found in various virtual platforms, which presents an innovative resource since these objects are complemented by the use of the educational robot Lego Mindstorms Ev3. Once the OVA'S have been socialized in the classroom, it can be concluded that it is a viable project, that it has an innovative perspective, thus fulfilling the expectations of the teacher and the students through a technological resource that can be found everywhere and can be Incorporate at all times and promote the teaching of the mathematics subject. This contribution has been recommended as relevant by the teacher of third year of EGB of the school "City of Zaruma".